2017
DOI: 10.1007/s10641-017-0665-3
|View full text |Cite
|
Sign up to set email alerts
|

Energetic requirements of green sturgeon (Acipenser medirostris) feeding on burrowing shrimp (Neotrypaea californiensis) in estuaries: importance of temperature, reproductive investment, and residence time

Abstract: Habitat use can be complex, as tradeoffs among physiology, resource abundance, and predator avoidance affect the suitability of different environments for different species. Green sturgeon (Acipenser medirostris), an imperiled species along the west coast of North America, undertake extensive coastal migrations and occupy estuaries during the summer and early fall. Warm water and abundant prey in estuaries may afford a growth opportunity. We applied a bioenergetics model to investigate how variation in estuari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…S2 of the Supplementary material). While physiological rates of ectotherms are often well described by an exponential relationship at low to intermediate temperatures, the relationship can break down towards the higher end of the temperature range, where feeding rate plateaus or even declines (Borin et al, 2017;Hung et al, 1993;Mizanur et al, 2014;Handeland et al, 2008;Lee et al, 2016). We hypothesized this mismatch in observed and predicted growth rates was due to leveling off of feeding rates at high temperatures.…”
Section: Deviation Of Growth At Higher Temperaturesmentioning
confidence: 96%
See 2 more Smart Citations
“…S2 of the Supplementary material). While physiological rates of ectotherms are often well described by an exponential relationship at low to intermediate temperatures, the relationship can break down towards the higher end of the temperature range, where feeding rate plateaus or even declines (Borin et al, 2017;Hung et al, 1993;Mizanur et al, 2014;Handeland et al, 2008;Lee et al, 2016). We hypothesized this mismatch in observed and predicted growth rates was due to leveling off of feeding rates at high temperatures.…”
Section: Deviation Of Growth At Higher Temperaturesmentioning
confidence: 96%
“…who suggested that the optimum was between 15°C to 19°C. Mayfield and Chech (2004) reported that food consumption, growth, and food conversion efficiency generally increased with temperature between 11 O C and 15 O C but stayed constant between 15 O C and 19 O C. However, a recent laboratory experiment (Poletto et al, 2018) found that green sturgeon reared at 19 O C grew at faster rates than those reared at 16 O C. In a recent simulation study, Borin et al (2017) reported that the mass-specific growth rate of a 20year old adult green sturgeon increased with temperature until 19 O C and declined above this temperature. In this study, the authors applied the Wisconson bioenergetics model (Hanson et al, 1997) to investigate the effects of different environmental factors, including temperature, on the consumption and growth potential of green sturgeon inhabiting Willapa Bay, Washington.…”
Section: The Debkiss Model Assumptions Parameter Estimation and Resmentioning
confidence: 98%
See 1 more Smart Citation
“…They are known to aggregate in the Washington estuaries in summer and are thought to feed there (Dumbauld, Holden, & Langness, ; Moser & Lindley, ). It may be that green sturgeon use estuaries to “recharge” after coastal migrations (Borin et al., ). Conversely, they may simply hold in these relatively predator‐free and physiologically‐benign zones to save energy or reduce predation risk (Moser & Lindley, ).…”
Section: Introductionmentioning
confidence: 99%
“…It may be that green sturgeon This article has been contributed to by US Government employees and their work is in the public domain in the USA. use estuaries to "recharge" after coastal migrations (Borin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%